Design of digital controller for an armature controlled motor using the digital approximation of a continuous controller/ Rahayu Yahaya - Yahaya, Rahayu (1999)
A digital controller for an armature-controlled motor is designed using the digital approximation of an analog controller. Several analog controllers are designed using analytical and root locus methods to meet the specifications. The analog controllers then have been designed include PID (Proportional-plus-Integral-plus-Derivative) and lead-lag controllers. MATLAB toolkit is used to obtain the responses of the system with the controllers. The responses of the system are specified in terms of maximum overshoot, steady state error, and the settling time. The best amongst them is used to obtain the digital controller via digital approximation. Six digital approximation methods are used. The results of the simulation of the closed-loop system for both the analog and digital controllers are then presented.